Makroökonomik Eine Einführung in die Theorie der Güter-, Arbeits- und Finanzmärkte - Arnold, Lutz (Mohr Siebeck, 2024)
Macroeconomics. An Introduction to the Theory of Goods, Labor and Financial Markets. 7th revised edition.
PublicationDate: 20240820
Keywords: Makroökonomik -- Finanzmarktökonomik -- Institutionenökonomik -- Lehrbücher -- Geld und Kredit -- Array